Revitalization of Nusantara Traditional Fashion: Integration of Sanggit Aesthetics and Design Thinking for the Preservation of Nusantara Culture - Sunarmi Sunarmi; Angga Kusuma Dawami; Linda Utami (Journal of Social Research, 2025)
The challenge of preserving traditional clothing such as jarik, kebaya, sarong, batik, songket, and weaving is increasingly marginalized by modernity and globalization. The main goal of this paper is to design and realize traditional fashion works based on virtual technology that are adaptive and contextual without losing their philosophical meaning and cultural value. The aesthetic approach of the archipelago in this study uses the concept of Sanggit work—a creative principle in traditional art that emphasizes the revitalization and adaptation of cultural values—as a strategy for revitalizing traditional clothing. This research also employs the Design Thinking method in five stages (Empathize, Define, Ideate, Prototype, and Test), strengthened by the Sanggit aesthetic approach, which emphasizes cultural revitalization in a contemporary form. The beauty of traditional fashion forms full of religious values is summed up as a concept of beauty that not only preserves visual heritage but also transforms it into ethical values and cultural identity. Five samples of traditional clothing from various regions—Central Java, Minangkabau, Maluku, Osing Banyuwangi, and Dayak Ngaju—formed the basis for the creation of the work. The results of the research, which went through the Sanggit process, produced traditional clothing originally used for ceremonial purposes, revitalized as work clothes and party clothes without eliminating the nuances and symbols of the archipelago's culture.